Music Genre Identification Using SVM and MFCC Feature Extraction - Septian Yogi Yehezkiel; Yohanes Suyanto (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2022)
Indonesia is a very diverse country because it has a vast territory and is occupied by millions of people from various tribe. Therefore, traditional music in Indonesia is also diverse because each region has its own culture and art. In this study, the author used the Support Vector Machine(SVM) pattern recognition to identify the Indonesian traditional music genre. This genre identification system is able to produce an accuracy of 83% using MFCC.Keywords : traditional music identification, Mel Frequency Cepstral Coefficient, Support Vector Machine.